Performance evaluation of a PMDC motor with battery storage control and MPPT based solar photovoltaic system - Khan Mohammad; Mohmmad Ahmad; Shoeb Azam Farooqui; Wajid Ali; Farha Khan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper analyzes and demonstrates the performance of a solar photovoltaic (SPV)-fed permanent magnet DC (PMDC) motor under various operating conditions. In this configuration, a 5HP PMDC is coupled to a SPV system and a boost converter has been interfaced between them to regulate the DC output voltage acquired from the SPV system. The switching pulse to the converter has been provided by the maximum power point tracking (MPPT) controller (P&O and INC) in order to acquire maximum and desired power across the DC link with varying irradiance. A battery energy storage system (BESS) is often used in association with this configuration caused by the non-linear nature of the SPV system and to overcome the volatility of the DC connection affected by environmental effects. For this purpose, a double loop PI controller is analyzed, and examined the DC link. Additionally, the operation of bidirectional DC-DC converter in buck and boost mode during battery charging and discharging is also performed. This operation ensures maintaining a constant and continuous power across the DC link to regulate the PMDC motor consistently. A comparison of results has also been presented for both incremental and conductance (INC) and P&O controllers. The mathematical modeling of configuration has been performed in MATLAB/Simulink software. The results and key findings have been tabulated and even elaborated graphically.